Pengaruh Variasi Konsentrasi Larutan Serbuk Daun Jeruk Purut (Citrus hystrix. DC) Terhadap Parameter Angka Kuman pada Peralatan Makan - Sri Ningrum; Munawar Raharja; Rahmawati Rahmawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2017)
Abstract: The effect of variation concentration of solution powder kaffir lime leaves (Citrus hystrix. dc) against the parameter of figure germ at eating utensils. The recommended disinfection process such as the use of heat and chemicals in a society generally not done because it takes a long time and expensive cost, as well as the excessive use of chemicals, can cause environmental pollution. Therefore, the necessary natural ingredients as a substitute as kaffir lime leaves. Based on the research results Sulistiyani, et al (2004) showed a rinsing by using kaffir lime leaves can decrease the number of microbes on eating utensils. This study aims to determine the effect of variation concentration of solution powder kaffir lime leaves (Citrus hystrix. DC) against the parameter of figure germ at eating utensils. This type of research is experimental, pretest-posttest design with the control group. The samples used were 42 swab samples plate tools. Methods of data collection based on the check out results from the number of figure germ (TPC) in the laboratory. Analysis of data using statistical test Paired t-test and correlation test. The results showed that the average total number of figure germs before treatment ranged from 44-73 colonies/cm2, and the average total number of figure germs after disinfection treatment with a solution of powdered kaffir lime leaves ranging between 6-50 colonies/cm2. Based Paired t-test is known that there are differences the average number of figure germ before and after treatment, where the average total number of figure germs after treatment is lower than the average number of figure germs before treatment with the percentage decrease ranging between 23-89%. Statistical analysis of the correlation test showed there is a relationship between variations in concentration of powder kaffir lime leaves with the number of figure germ on the plate. Kaffir lime leaves contain chemical compounds polyphenols, flavonoids, essential oils, tannins and alkaloids that have a pharmacological effect as an antiseptic, so it can be used as a disinfectant to wash eating utensils. Keywords: Kaffir lime leaves (Citrus hystrix. DC); figure germs.